Neck Vibration Proprioceptive Postural Response Intact in Progressive Supranuclear Palsy unlike Idiopathic Parkinson’s Disease - Kammermeier, Stefan; Dietrich, Lucia; Maierbeck, Kathrin; Plate, Annika; Lorenzl, Stefan; Singh, Arun; Bötzel, Kai (Frontiers in Neurology, 2017)
Progressive Supranuclear Palsy (PSP) and late-stage Idiopathic Parkinson’s Disease (IPD) are neurodegenerative movement disorders resulting in different postural instability and falling symptoms. IPD falls occur usually forward in late-stage, whereas PSP falls happen in early stages, mostly backward, unprovoked and with high morbidity. Postural responses to sensory anteroposterior tilt illusion by bilateral dorsal neck vibration were probed in both groups versus healthy controls on a static recording posture platform. Three distinct antero-posterior body-mass excursion peaks (P1-3) were observed. 18 IPD subjects exhibited well-known excessive response amplitudes, whereas 21 PSP subjects’ responses remained unaltered to 22 control subjects. Neither IPD or PSP showed response latency deficits, despite brainstem degeneration especially in PSP. The observed response patterns suggest PSP brainstem pathology might spare the involved proprioceptive pathways and implies viability of neck vibration for possible biofeedback and augmentation therapy in PSP postural instability.